2018
DOI: 10.1021/acs.analchem.8b03562
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enrichment and Quantification of N-Terminal Glycine Peptides via Sortase A Mediated Ligation

Abstract: The identification and quantification of low-abundant proteins are always impeded by high-abundant proteins in proteomic analysis because of the extreme complexity of peptide mixtures and wide dynamic range of protein abundances. Here, we developed a novel approach to enrich and quantify N-terminal glycine peptides through sortase A mediated ligation. This strategy was based on the formation of a covalent bond between the sortase A recognition motif LPXTG and a N-terminal glycine residue. Also, the quantificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Previously, it was thought that the substrates of sortase A require multiple consecutive glycine residues at the N‐terminus [13] . However, it was found that the ligation could also effectively happen on peptides with other amino acid residues immediately after N‐terminal glycine [9,11] . In the current datasets, only 8–10 % of the amino acid residues immediately after the terminal glycine are glycine (Figure 1D).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Previously, it was thought that the substrates of sortase A require multiple consecutive glycine residues at the N‐terminus [13] . However, it was found that the ligation could also effectively happen on peptides with other amino acid residues immediately after N‐terminal glycine [9,11] . In the current datasets, only 8–10 % of the amino acid residues immediately after the terminal glycine are glycine (Figure 1D).…”
Section: Resultsmentioning
confidence: 60%
“…The enzyme was widely used for protein engineering and the labeling of cell‐surface proteins [9–10] . “X” can be any amino acid residue, and arginine was chosen because it provides a trypsin cleavable site in the sequence for eluting enriched peptides from the resins [11] . The mixture was incubated for only 1 h to minimize possible protein cleavages by endogenous proteases, which were inhibited by the addition of protease inhibitor cocktail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the previous reports in which sortase A can mediate the ligation with peptides containing any amino acid residues at the position next to N-terminal glycine. [11] The occurrence of glycine in the human proteome is around 7 %. [14] A slightly higher frequency of glycine identified at the position next to Nterminal glycine using all three types of sortase A suggests that the enzyme may have a slightly higher efficiency in catalyzing the ligation of peptides with consecutive glycines at the N-terminus.…”
Section: Evaluating the Effectiveness Of Different Types Of Sortase A...mentioning
confidence: 99%